The relationship between the scarf ratio and subsequent motor performance in infants born preterm - Raweewan Lekskulchai (2018)
The relationship between the scarf ratio and subsequent motor performance in Thai infants born preterm was the focus of this study. The scarf ratio was measured in 61 infants at 36 and 40 weeks postconceptional age (PCA). At 40 weeks PCA, one-, two-, three-, and four-months adjusted age, the infants were evaluated using the Test of Infant Motor Performance. Pearson product moment correlations revealed significant positive correlations between the scarf ratio and the infants' later motor performance. Because the scarf ratio can be a useful measure of shoulder girdle muscle tone, it may provide a valuable indicator of subsequent motor performance in infants born preterm who might be considered to be at risk for developmental delay.